Edukasi Kebencanaan dalam Meningkatkan Kesiapsiagaan Bencana Banjir pada Siswa Sekolah Dasar: Disaster Education in Improving Flood Disaster Preparedness among Elementary School Students in Banjarmasin - Trifianingsih, Dyah; Sitompul, Dania Relina; Rahman, Aulia (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Floods are the most common type of disaster in the world. Flood disaster preparedness in the community still rarely gets attention. While children are one of the groups at risk in disasters, they can also take an active part in disaster management, provided that the opportunity is given. Disaster education is an important aspect of disaster management, and it involves children who are expected to help create better disaster resilience, flood awareness, and preparedness. This community service uses a method by implementing a disaster education program for children using an interactive lecture method with an audio-visual approach. Community service was carried out on October 14, 2024, with the children of SDN 7 Pelambuan Banjarmasin as the target of the activity. Evaluation was carried out by giving participants questionnaires at the beginning (pre) and end (post). The results of the activity showed an increase in knowledge of flood disasters after being given education, with a P-value of 0.000 in the Paired Sample Test.